2024
DOI: 10.1139/cgj-2023-0219
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing hydraulic fracturing for in-situ remediation in low-permeability soils: A comprehensive investigation of fracture propagation

Zhuang Cui,
Bing Hou

Abstract: Enhancing the complexity of the hydraulic fractures to provide a wide channel for the injection of the agent is crucial for remediating low-permeability contaminated sites. This study involved a physical simulation experiment of large-scale true triaxial hydraulic fracturing in undisturbed soil, as well as field fracturing tests, to investigate fracture initiation mechanisms and the influence of different factors on fracture propagation. The study revealed a unique failure mode for low-permeability soils chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Laboratory experimental studies that can realistically consider initial conditions such as the water content and stress state of low-permeability contaminated soils and provide guidance parameters such as oxidant concentration and total oxidant demand (TOD) for remediation sites under fracking conditions are still scarce. Previous studies have shown that hydraulic fracturing can create horizontal fractures, which may appear as flat-lying circular disks filled with coarse-grained proppant in the field [31,32,35]. These disks can be reduced to circular fracture layers with a certain thickness and high permeability; thus, the oxidant transport between two parallel fracture layers can be considered a one-dimensional transport.…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory experimental studies that can realistically consider initial conditions such as the water content and stress state of low-permeability contaminated soils and provide guidance parameters such as oxidant concentration and total oxidant demand (TOD) for remediation sites under fracking conditions are still scarce. Previous studies have shown that hydraulic fracturing can create horizontal fractures, which may appear as flat-lying circular disks filled with coarse-grained proppant in the field [31,32,35]. These disks can be reduced to circular fracture layers with a certain thickness and high permeability; thus, the oxidant transport between two parallel fracture layers can be considered a one-dimensional transport.…”
Section: Introductionmentioning
confidence: 99%